Histologic study of furcation perforations treated with MTA or Super EBA in dogs' teeth - (:unkn) unknown (MOSBY-ELSEVIER, 2005)
Objective. The aim of this study was to investigate the histologic response to MTA or Super EBA when used for the repair of furcation perforations in dogs teeth. Study design. Ninety mandibular premolar and molar teeth of 9 mongrel dogs were used in this Study. The teeth were divided into 3 groups. Seventy-two teeth were repaired with either MTA or Super EBA (36 each), and 18 teeth were not repaired and used as negative controls. All groups were histologically examined at 1 month, 3 months, and 6 months after treatment. Histologic evaluation was done with regard to inflammation and type of healing. Results. The Super EBA group showed moderate inflammation in 1 month; the inflammation decreased over time, but most of specimens showed inflammatory reaction from mild to severe at the end of 6 months. The perforation area was filled by connective tissue in specimens in which no inflammation was seen. In the MTA group, mild inflammation was seen in 1 month, it decreased in 3 months, and no inflammation was detected in 6 months. New cementurn formation was taken in place in 4 specimens in 1 month, in 8 specimens in 3 months, and in all specimens in 6 months. Conclusions. MTA showed less inflammation than Super EBA. MTA specimens showed healing with new cementurn formation in the perforation area, whereas Super EBA specimens in which no inflammation was seen showed connective tissue healing.
Keywords: MINERAL TRIOXIDE AGGREGATE; LATERAL ROOT PERFORATIONS; END FILLING MATERIAL; CALCIUM HYDROXIDE; SEALING ABILITY; ENDODONTIC PERFORATIONS; TRICALCIUM PHOSPHATE; REPAIR; AMALGAM; HYDROXYLAPATITE